Insights for Argumentation Theory from a Cognitive-Motivational Approach to Emotions - Santibáñez, Cristián (Człowiek i Społeczeństwo, 2026)
This paper examines Miceli and Castelfranchi’s (2015; hereafter M&C) theory of emotion to explore how a cognitive-motivational analysis of emotional functioning can interact with established conceptual approaches in mainstream argumentation theory, with particular attention to argument reconstruction and interpretation. The discussion begins by outlining the principal ideas presented by M&C, focusing on how their cognitive-motivational framework provides insights into the mechanisms underlying emotions. These concepts are then applied specifically to argumentation theory, demonstrating the relevance of M&C’s approach within this domain. The analysis culminates with a detailed example illustrating the integration of both perspectives, highlighting the practical implications of combining cognitive-motivational analysis with argumentation theory. From the discussion and the example provided, two key ideas emerge. First, employing a cognitive-motivational anatomy of emotion makes it easier to reconstruct and interpret the implicit elements within arguments. Second, incorporating the conceptual frameworks of persuasion through arousal of emotions and persuasion through appeal to anticipated emotions clarifies the role that specific emotions play in the structure of an argument.